Evaluation of Several Methods of Determining Drainage Modulus in Wetland Ricefield Sei Beras Sekata Regional Sunggal Deli Serdang District - Zulhakki Zulhakki; Sumono Sumono; Lukman Adlin Harahap; Edi Susanto (Jurnal Rekayasa Pangan dan Pertanian, 2013)
The aim of this study was to quantify and to compare the modulus values ​​of wetland ricefield drainage in the village of Sei Beras Sekata. Drainage modulus value is used as a reference to throw out water from the wetland ricefield. Drainage modulus values ​was ​calculated by three methods i.e plotting maximum daily rainfall, daily inundation simulations with a daily water balance in the mapped fields, and using the formula of the Department of Public Works. It was found from the research, that the drainage modulus values on daily maximum rainfall plotting methods was 29 mm day-1, the daily inundation simulation methods with high daily water balance mapped fields was 40.3 mm day-1, and formula of the Department of Public Works was 61,2 mm day-1. Key words: drainage modulus, wetland ricefield, Sei Beras Sekata